Application of Cold Chain and Freezing Load Calculation of Frozen Flower Octopus (Octopus sp) at PT. X, Makassa, South Sulawesi - Salampessy, Randi Bokhy; P. Handoko, Yudi; A. Utari, Nurul (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
The economic value of octopus (Octopus sp) makes octopus one of the export commodities from Indonesia. The increase in the value of octopus exports was due to high demand in the US, Japan and European Union markets. Storage at cold temperatures can maintain quality and if stored at frozen temperatures can last for a long time. Cooling load is the amount of heat released or transferred by the air conditioning system over time. The purpose of this study was to determine the processing flow of frozen flower octopus, to determine product temperature, water, and room temperature, to determine the organoleptic and microbiological quality of raw materials and final products. This research was conducted at PT. X in March to June 2021. The conclusions of this study are: The processing of frozen flower octopus consists of 16 process flows, namely acceptance, sorting size and quality, washing 1, salting (soaking), weeding, washing 2, weighing 1, product formation. , freezing, weighing 2, metal detector, glazing, weighing 3, packaging, cold storage, and stuffing. The application of the cold chain has met the company's requirements. The results of organoleptic quality testing of raw materials and final products have a value of 8, and the microbiological quality testing of ALT, E. coli, and Salmonella meets SNI standards. The heat load of the product is found to be between 5.60 to 10.68 kilowatts and the non-product heat load is normal.